EVALUATION OF BONE MINERAL DENSITY IN PATIENTS WITH PLAQUE PSORIASIS WITHOUT ARTHROPATHY - Rafet Koca,; H. Cevdet Altınyazar,; M. Dilşad Kılınçarslan,; Gamze Açıkgöz,; Ülkü Koç, (Archives of Rheumatology, 2004)
Psoriasis is a chronic, recurrent, inflammatory and hyperproliferative skin disease. Osteoporosis is characterized by decrease of bone mineral density (BMD) and bone matrix. Reduced BMD is a major risk factor for osteoporotic fracture. The aim of this study is to investigate BMD (using Z score) in patients with moderate and severe plaque psoriasis without arthropathy. Forty-three patients (12 males, 31 females and mean age 38.2) diagnosed as plaque psoriasis without joint involvement and 30 healthy subjects (9 males, 21 females and mean age 38.6) were included to this study. BMD was measured with dual X-ray absorptiometry at the lumbar spine (L2-4), femur and left forearm of all patients and healthy subjects. There were no significant differences in the mean BMD of L2-4, femur and left forearm between patients and healthy subjects (for each region p>0.05). Both groups were divided into two subgroups according to the age of the subjects as a younger and older than 40-year-old. No significant differences were detected in comparisons between these subgroups (p>0.05). Furthermore, we have not found significant differences in BMD between patients and healthy subjects which were postmenopausal (p>0.05). As a result, this study indicoted that cortical or trabecular bone density was not affected in patients with moderate and severe plaque psoriasis without joint involvement.